Application of "blockchain" and "smart contract" tehnology in international payments : the case of reimbursement banks - Pečarić, Mario (Array, 2020)
The aim of this paper is to find alternative method of executing reimbursement loan, as a form of documentary loan, that is, to investigate new digital technology methods (fintech) to improve the efficiency of the international exchange. Reimbursement loans are often used to credit the trade of overseas goods. The reason of such case is that the shipment of goods by the maritime transport requires a significant amount of time and those trades are often associated with high financial amounts. Since international trade (exchange) is a kind of a generator of society’s progress, it is necessary to explore the possibilities for making international payment cheaper, more efficient and more secure. In this case, we based our research on the implementation of modern technologies, more precisely “blockchain”/DLT (Distributed Ledger Technology) and “smart contracts”. The new reimbursement loan model presented in the paper is based on the aforementioned technologies. It could potentially change not only the documentary lending techniques, but also, eventually, overall financial paradigm. The effectiveness of the application of modern technologies is proven comparing the results of the so called conventional and unconventional reimbursement credit model on a real case involving two companies in Indonesia and Singapore. The paper also tackles on the further implementation of “smart contract” technology and “blockchain”/DLT, thus considering the potential impact of these technologies on overseas trade, credit markets and financial institutions. Finally, the paper argues on the limitations in implementing this new technique (e.g. legal, political and technical challenges).